Reprodutibilidade teste-reteste da tarefa de levantar-se do solo em idosos. - Ramos Maciel, Marina; Fernandes Souza, Bárbara Laís; de Santana Mota, Camila; de Queiroz, Robson Felipe; Rodrigues de Assis, Matheus; Peralta Safons, Marisete; Cattuzzo, Maria Teresa; Santos de Santana, Frederico (Fisioterapia Brasil, 2022)
The aim of the study was to determine the reproducibility of the supine-to-stand task analysis according to Haywood et al. protocol. Twenty volunteers (healthy elderly 72.87 ± 6.51 years; BMI 26.8 ± 4.66 kg/m²; height 1.6 ± 0.09 m) were selected and performed the following functional capacity tests: Timed Up and Go, unipodal support and handgrip dynamometry, plus the supine-to-stand task. Two attempts were made at intervals of 7 to 15 days, filmed and analyzed by Kinovea® software. Finally, the test-retest reproducibility of the supine-to-stand task was evaluated by means of Kappa Coefficient, with significance level adopted p ≤ 0.05. The results showed reproducibility for upper limbs of K = 0.481, axial region of K = 0.519 and lower limbs of K = 0.851, respectively, all with p < 0.001. Therefore, we conclude that the reproducibility of the of the supine-to-stand task in the elderly, according to Haywood et al. was considered moderate, in general.